The role of vitamin D in diabetic foot ulcer; an umbrella review of meta-analyses - Liu, Lu; Zhang, Fan; Jamali, Mehrdad; Guimarães, Nathalia Sernizon; Radkhah, Nima; Jamilian, Parmida; Wang, Qian (Frontiers in Nutrition, 2024)
Background: Complications related to diabetic foot ulcers (DFU) due to diabetes are increasing. One of the factors influencing the management and treatment of complications related to DFU is the vitamin D serum levels of patients. Therefore, we sought to comprehensively review meta-analyses from randomized controlled trials and observational studies examining the link between serum vitamin D levels and DFU outcomes in diabetic patients.We searched PubMed, Scopus, and ISI Web of Science until September 2024 and extracted the required data from related articles according to Inclusion criteria. The certainty of the evidence and the quality of conduct of the published meta-analyses were rated using the ASMTAR 2 tools, respectively.Result: A total of 8 meta-analyses studies that met inclusion criteria were included. Based on the obtained results, it has been noted that individuals with DFU exhibit serum vitamin D levels significantly lower, ranging from -7. 14 (5.44, 8.83) to -0.93 (95% CI: 0.17, 1.68) ng/ml, compared to those with diabetes but without DFU. Furthermore, individuals exhibiting severe vitamin D deficiency are found to be at least 1.82 times more susceptible to developing DFU. Conversely, administering varying doses of vitamin D supplementation has been shown to positively affect the size and number of ulcers in DFU patients.This study suggests a potential link between lower levels of vitamin D in the blood and the risk of DFU, hinting at the benefits of vitamin D supplementation in improving outcomes associated with DFU. However, caution is warranted due to the potential bias present in the included studies.